Pengaruh Persepsi Wajib Pajak Usaha Mikro Kecil Menengah Terhadap Pembayaran dan Pelaporan Pajak Secara Online Pada Kantor Pelayanan Pajak (KPP) Pratama Seberang Ulu Palembang - Septiana Wulandari; Endang Sri Mulatsih (P3M STIE Mulia Darma Pratama, 2019)
Perception of UMKM taxpayers is an internal process that allows choosing, organizing, interpreting stimuli from the environment and the process influences behavior. Individuals or entities, including taxpayers, tax cutters, and tax collectors, who have tax rights and obligations in accordance with the provisions of taxation laws and regulations. Factors that can influence the acceptance of information technology by users can use the Technology Acceptance Model (TAM). TAM is a model that explains factors that can affect users (tax employees), when using or utilizing information technology. Online tax payments and reporting are a means for the Directorate General of Taxes (DGT) to oversee electronic payments and reporting called e-payment. This research was conducted at the KPP Pratama Seberang Ulu Palembang. The research method used is associative method. Data collection is done by means of interviews, questionnaires, and literature studies. Data sources used are primary data and secondary data. The results of the respondents' research on the perception of MSME taxpayers who were examined who answered strongly disagree (0.5%), disagree (5.5%), answer doubt (50%), who answered agree (35%) and answered strongly agree (9%). And respondents about online tax payments and reporting that answered strongly disagree (0%), disagree (4.5%), answer doubtfully (42%), who answered agree (40%) and answered very agree (13.5%). From the results of the classic assumption test there are no symptoms of autocorrelation, multicollinearity, and heteroscedasticity. Simple regression equation Y = 11,332 0,392 X. From the results of hypothesis testing shows that Ho is rejected or accepts HA means that the perception of MSME taxpayers affects the payment and tax reporting online. The coefficient of determination of value is 0.105 or 10.5%. This indicates that the influence of the UMKM taxpayer perception variable on online tax payments and reporting is 10.5%. The remaining 89.5% is influenced by variables not included in the study.